2000
DOI: 10.1067/mcp.2000.108947
|View full text |Cite
|
Sign up to set email alerts
|

Morphine clearance and effects in newborn infants in relation to gestational age

Abstract: Morphine should be used with caution in prematurely born infants because of its low clearance, which correlates with gestational age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 28 publications
1
39
1
Order By: Relevance
“…The surgical procedure, which can induce haemodynamic perturbation, together with the effects of anaesthesia, may have attenuated the already low cerebral oxygenation. There is also evidence that the pharmacodynamics of medication, particularly opioids, are different during different postmenstrual and postnatal ages,23 24 giving rise to excessive sufentanyl levels in some extremely preterm patients. This could have had a negative impact on the blood pressure of these infants.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical procedure, which can induce haemodynamic perturbation, together with the effects of anaesthesia, may have attenuated the already low cerebral oxygenation. There is also evidence that the pharmacodynamics of medication, particularly opioids, are different during different postmenstrual and postnatal ages,23 24 giving rise to excessive sufentanyl levels in some extremely preterm patients. This could have had a negative impact on the blood pressure of these infants.…”
Section: Discussionmentioning
confidence: 99%
“…In our small study population, we could not demonstrate a relationship between the observed changes in cerebral hemodynamics and oxygenation and GA or BW. However, since the clearance of midazolam [27] and morphine [28] is related to GA and BW, a correlation is imaginable.…”
Section: Discussionmentioning
confidence: 99%
“…31 Some studies suggest that babies require higher plasma concentrations than older children or adults to receive pain relief, 32 although other studies disagree. [33][34][35][36] In the past, morphine was thought to be a pure opioid agonist, but this theory was disproven long ago. 37 Morphine has a ceiling effect; after a certain therapeutic level has been reached, higher doses will produce more adverse effects rather than increased analgesia.…”
Section: Morphinementioning
confidence: 99%